Developing software for dynamic analysis of fractal time series - Gan, Zi Yan (2017)
The ability to predict the future often seems far-fetched one will never know with absolute certainty. However, many things in real-life occur for a reason. At many times, these reasons are a surmount of multiple indicators that has passed, present and yet to come. Many people put much time and effort in trying to predict the future and Harold Edwin Hurst was one. He studied the River Nile all his life to try and determine the floods and droughts of the River. Eventually he came up with an expression which could determine a coefficient that can relate the long-term range dependence of a series. The calculation of this series is a tedious and gruelling process which Hurst dedicated his life. Thus, using modern tools such as the computer, we will be able to create a program to calculate the complex algorithm in a matter of minutes. This paper shows the various considerations as well as the documentation of the software created to calculate the Hurst Exponent as well as other tools as accompaniment. The code is provided in the appendix.